Projecting Permafrost Thaw of Sub‐Arctic Tundra With a Thermodynamic Model Calibrated to Site Measurements. Issue 6 (16th June 2021) - Garnello, A.; Marchenko, S.; Nicolsky, D.; Romanovsky, V.; Ledman, J.; Celis, G.; Schädel, C.; Luo, Y.; Schuur, E. A. G.
Abstract: Northern circumpolar permafrost thaw affects global carbon cycling, as large amounts of stored soil carbon becomes accessible to microbial breakdown under a warming climate. The magnitude of carbon release is linked to the extent of permafrost thaw, which is locally variable and controlled by soil thermodynamics. Soil thermodynamic properties, such as thermal diffusivity, govern the reactivity of the soil‐atmosphere thermal gradient, and are controlled by soil composition and drainage. In order to project permafrost thaw for an Alaskan tundra experimental site, we used seven years of site data to calibrate a soil thermodynamic model using a data assimilation technique. The model reproduced seasonal and interannual temperature dynamics for shallow (5–40 cm) and deep soil layers (2–4 m), and simulations of seasonal thaw depth closely matched observed data. The model was then used to project permafrost thaw at the site to the year 2100 using climate forcing data for three future climate scenarios (RCP 4.5, 6.0, and 8.5). Minimal permafrost thawing occurred until mean annual air temperatures rose above the freezing point, after which we measured over a 1 m increase in thaw depth for every 1 ° C rise in mean annual air temperature. Under no projected warming scenario was permafrost remaining in the upper 3 m of soil by 2100. We demonstrated an effective data assimilation method that optimizes parameterization of a soil thermodynamic model. The sensitivity of local permafrost to climate warming illustrates the vulnerability of sub‐Arctic tundra ecosystems to significant and rapid soil thawing. Plain Language Summary: Across Arctic environments, cold temperatures maintain perennially frozen ground, which store ancient carbon from dead plants. Climate warming is thawing this ground, potentially transferring carbon from the soil into the atmosphere, further contributing to planet warming. How this ground thaws varies across the landscape due to complex soil properties. We created a model for predicting how much the ground would thaw by 2100. This model used seven years of measurements made at an Alaskan tundra research site near Denali Park for calibration. The model was accurate over this seven‐year period, producing results which closely match our observed data. Our model showed that over 1 m of ground is expected to thaw for every 1 ° C sustained rise in air temperature, leading to 5–13 m of ground thawing to occur by 2100, dependent on the extent of air warming. This result demonstrated a novel method for obtaining precise local estimates of ground thawing that rely on site measurements and highlights the extreme vulnerability of Arctic ground to thawing in the face of climate change. This study is important because it allows for local predictions of Arctic ground thawing, which are a key component for the full extent of soil carbon loss into the atmosphere. Key Points: We used seven years of site data to calibrate a soil thermodynamic model to forecast permafrost thaw for an Alaskan tundra experimental site Despite variability in parameters' estimates, model simulations tightly matched seasonal thaw values measured over the calibration period No climate scenario retained permafrost in the upper 3 m of soil by 2100 and permafrost depth correlated with degree of sustained air warming